Staycation During COVID-19 Pandemic with Virtual Tourism: Tele-Tourist Attitude Toward Experience in Cultural Heritage Destination - Bafadhal, Aniesa Samira (Graduate School, Universitas Brawijaya, 2021)
Malang City, Indonesia, is known as the Paris van oost Java and was officially named the City of Heritage because of the high interest of domestic and foreign tourists to trace the history and antique architecture of the city. However, travel restriction policies in various countries also demanded the solidarity of tourists to stay at home, avoiding crowds, and delaying travel plans during the COVID-19 pandemic. It clearly causes the tourism sector to be heavily affected. Therefore, it is necessary to manage cultural heritage tourism destinations that can allow tourists to do a staycation in sophisticated form and considering the carrying capacity more according to the COVID-19 safety protocol. As a solution, this research used the R&D method with mixed methods approach consist of observation, visual analysis, and survey experimental to produce web-based virtual tourism (web-VR) for ancient and astonishing The Great Mosque of Jami' Malang. The content was further confirmed using field experiments analyzed by Generalized Structured Component Analysis (GSCA) involving 30 tele-tourists. The results of this study indicate that the virtual experience of tourists, which consists of immersiveness and telepresence after visiting the virtual destination, has an effect on the attitude of tele-tourist. Therefore, virtual tourism can be considered complementary to actual visits, visitor management, as well as preserve destination sustainability. Keywords: COVID-19, immersion, telepresence, tele-tourist attitude, virtual experience, virtual tourism.